KOMPONEN UTAMA DALAM INSTRUMEN AKREDITASI SEKOLAH/ MADRASAH: KAJIAN TERHADAP MUTU LULUSAN DAN PROSES PEMBELAJARAN - Junaidi; Abdurrazak; Husnul Yaqin; Hilmi Mizani (CV. ADIBA AISHA AMIRA (ADISAM PUBLISHER), 2026)
This article examines two main components in the school/madrasah accreditation instrument, namely graduate quality and the learning process. Accreditation is an external quality assurance mechanism that plays a crucial role in Indonesia’s national education system, implemented by the National Accreditation Board for Schools/Madrasahs (BAN-S/M). Using a literature review approach and policy analysis, this article analyzes the standards, indicators, and instruments used to assess graduate quality and the learning process at the school and madrasah levels. The findings indicate that graduate quality is measured through the achievement of cognitive, affective, and psychomotor competencies that reflect the Graduate Competency Standards (SKL), while the learning process is evaluated based on planning, implementation, and assessment practices that refer to the Process Standards. These two components are interconnected and jointly serve as key determinants of educational quality in schools/madrasahs. The article concludes that improving graduate quality can only be achieved through strengthening the learning process in a systematic, innovative manner that is oriented toward the holistic development of students’ potential.